Metastasectomy for colorectal pulmonary metastases: A survey among members of the european society of thoracic surgeons - BATIREL, HASAN FEVZİ (My University, 2023)
OBJECTIVES: Surgical management of pulmonary metastases in colorectal cancer patients is a debated topic. There is currently no consensus on this matter, which sparks considerable risk for international practice variation. The European Society of Thoracic Surgeons (ESTS) ran a survey to assess current clinical practices and to determine criteria for resection among ESTS members.METHODS: All ESTS members were invited to complete an online questionnaire of 38 questions on current practice and management of pulmonary metastases in colorectal cancer patients.RESULTS: In total, 308 complete responses were received (response rate: 22%) from 62 countries. Most respondents consider that pulmonary metastasectomy for colorectal pulmonary metastases improves disease control (97%) and improves patients\" survival (92%). Invasive mediastinal staging in case of suspicious hilar or mediastinal lymph nodes is indicated (82%). Wedge resection is the preferred type of resection for a peripheral metastasis (87%). Minimally invasive approach is the preferred approach (72%). For a centrally located colorectal pulmonary metastasis, the preferred form of treatment is a minimally invasive anatomical resection (56%). During metastasectomy, 67% of respondents perform mediastinal lymph node sampling or dissection. Routine chemotherapy is rarely or never given following metastasectomy (57% of respondents).CONCLUSIONS: This survey among the ESTS members underlines the change in practice of pulmonary metastasectomy with an increasing tendency in favour of minimally invasive metastasectomy and surgical resection is preferred over other types of local treatment. Criteria for resectability vary and controversy remains regarding lymph node assessment and the role of adjuvant treatment.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Cardiovascular; Surgery Medicine Sciences; Health Sciences; KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); SOLUNUM SİSTEMİ; CERRAHİ; CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); RESPIRATORY SYSTEM; SURGERY; Solunum Bakımı; Cerrahi; Akciğer ve Solunum Tıbbı; Kardiyoloji ve Kardiyovasküler Tıp; Respiratory Care; Surgery; Pulmonary and Respiratory Medicine; Cardiology and Cardiovascular Medicine; Lung metastases; Metastasectomy; Video-assisted thoracic surgery; Lymphadenectomy; Survey; Colorectal metastases; CANCER; RESECTION; Lung metastases; Metastasectomy; Video-assisted thoracic surgery; Lymphadenectomy; Survey; Colorectal metastases